Marketing Strategy to increase Competitive Advantages on Mobile Phone Service Business for ETL Company Limited’s in Luang Prabang Oudom - SALIKA, OUDOM; KEOBOUALAPHETH, Soulideth (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Currently telecom business and telecommunications technology is changing rapidly resulting in consumers’ are in-depth understanding of products or service quality, quality assurance, ease of use, and low cost of services, These are major reasons why, executives and marketers need to new strategies that meet their customers’ demand and make a difference compared to other competitors. To identity the marketing strategy to increase competitive advantages on mobile phone service business for ETL Company Limited’s in LuangPrabang. The purpose of the current study were to: (1) study the market share of the mobile service business, (2) analyze the operation environment impacting the business, and (3) to determine the marketing strategies of the ETL Company limited. This study adopted the qualitative research, which interviews are primarily used to collect data from executives and secondary data in the form of activity reports of ETL Company limited business in LuangPrabang are also gathered. The findings found that ETL Company limited had 3.80% market share in mobile phone business in LuangPrabang, which is lower than the Star Telecom Company and Lao Telecom Public. When analyzing the business environment (SWOT) both internally and externally has seen that, the weaknesses and positions have a variety of opportunities. In addition to identifying strategic marketing management services ETL Company limited in LuangPrabang 2019 has witnessed that number of the clients in terms of service network phones tend to increase because there is high competition from rival companies, for instance, Lao Telecom company public and the Star Telecom company competition. Thus, the ETL Company limited has applied low-cost strategies than competitors and make a wide range of products to take more advantages of the competition in the future.